2017
DOI: 10.1111/1440-1630.12393
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of handwriting development: Pen‐grip kinetics in handwriting tasks and its relation to fine motor skills among school‐age children

Abstract: A novel system is proposed for analysing school-age children's force control while handwriting. We observed the development of force control in relation to pen grip among the children with different ages in this study. The findings suggested that manipulation skill may be crucial when children are establishing their handwriting capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
4
18
2
1
Order By: Relevance
“…Such children often appear clumsy and uncoordinated. 4 , 5 Motor coordination problems have previously been labelled ‘clumsy child syndrome’, ‘non-cerebral-palsy motor-perception dysfunction’, ‘minor neurological dysfunction’ or ‘dyspraxia of childhood’. 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such children often appear clumsy and uncoordinated. 4 , 5 Motor coordination problems have previously been labelled ‘clumsy child syndrome’, ‘non-cerebral-palsy motor-perception dysfunction’, ‘minor neurological dysfunction’ or ‘dyspraxia of childhood’. 6 …”
Section: Introductionmentioning
confidence: 99%
“… 8 Poor fine motor skills can make cognitive learning and performance more difficult because of the involvement of fine motor skills in cognitive activities. 5 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…Compared with the forces applied from the hand toward a surface, researchers have focused on the forces applied from the digits and pen tip, where therapy practitioners can directly intervene. Previous literature on this topic has suggested that pen-tip force is not grade related [13,18]. However, it may be influenced by task demands and specific writing characteristics such as writing speed [18].…”
Section: Introductionmentioning
confidence: 97%
“…This situation raises a question as to how therapy practitioners should instruct children to apply an appropriate amount of force if the correct amount to be applied remains unknown. Accordingly, a few research groups have attempted to measure the invisible force from fingers with custom-made kinetic pens to present the actual forces applied to the pen [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This altered motor command resulted from stressful environments (Van Gemmert & Van Galen, 1997) or was observed in children with neurodevelopmental disabilities (Smits-Engelsman et al, 2003). Although the grip is important because it allows the fine movements necessary for writing, several studies failed to find a consistent relationship between pen grip biomechanical factors and handwriting legibility (e.g., Lin et al, 2017;Parush et al, 1998;Rosenblum et al, 2006).…”
Section: Introductionmentioning
confidence: 99%